Kajian Literatur : Etnografi Digital Sebagai Cara Baru Dalam Pencarian Data Dalam Proses Perencanaan Arsitektur - Effendi, Andrey Caesar; Purwanto, LMF (Aksen : Journal of Design and Creative Industry, 2021)
The use of digital technology today can be said to be inseparable in our daily lives. Digital technology isslowly changing the way we communicate with others and the environment. Socialization that is usuallyface-to-face in the real world now can be done to not having to meet face-to-face in cyberspace. Thisliterature review aims to see a change in the way of obtaining data that is growing, with the use of digitaltechnology in ethnographic methods. The method used in this paper is to use descriptive qualitativeresearch methods by analyzing the existing literature. So it can be concluded that the use of digitalethnography in the architectural programming process can be a new way of searching for data at thearchitectural programming stage.